Deriving The Canonical Equivalent Circuit For Small Signal & Low Frequency Ac Model For The Sepic And Zeta PWM Dc-dc Converters With Two-port Network - Kassick, Enio V. (Eletrônica de Potência, 2011)
PWM dc-dc converters operating in Continuous Conduction Mode (CCM) perform similar basic functions despite the topology of which one. The canonical equivalent circuit of small signal & low frequency ac model permits to analyze converter behavior in a general manner, without the need to make reference to a specific topology. For Buck, Boost, Buck-Boost and Cuk topologies the “plug-in” parameters of the canonical model can be easily found just by circuit manipulation using very simple circuit analysis techniques. For the Sepic (Single-Ended Primary Inductor Converter) and Zeta topologies, utilization of the same procedure fails and one cannot arrive to the canonical model. To overcome this barrier, some authors indicate the need to apply circuit synthesis techniques which are not always familiar to many engineers. It will be shown that it is possible to arrive to the canonical model of this two converter topologies by using the well-known two-port network (quadripoles) circuit analysis technique.